THE EFFECTIVENESS OF STRUCTURAL DA'WAH FRIDAY WORSHIP IN GOWA REGENCY IN IMPROVING THE QUALITY OF COMMUNITY PIETY - Suhardi, Suhardi (PT Altin Riset Publishing, 2025)
Structural da'wah is da'wah carried out by the government, to improve the quality of faith of employees and the community, and to create professional and conducive jobs. High faith can encourage employees and the community to increase their piety to Allah. In this study, the role of structural da'wah in improving the quality of community worship in the Gowa district will be revealed. The type of research is qualitative research using the da'wah science approach. The sources of data for this research are scholars, umara, employees, and the community. The data collection methods used are observation, interviews, and documentation. The results of this study show that: the da'wah program of Friday worship in Gowa district is effective in improving the spiritual quality of the community. In the field of faith, mad'u is to stay away from superstition, bid'ah, and superstition. In the field of worship, namely the spirit of mad'u in prospering mosques and mushallahs, both congregational obligatory prayers and sunnah prayers, the more active in dhikr, and actively reading the Qur'an.